2017
DOI: 10.1097/hjh.0000000000001455
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the influence of lung function on vascular health from adolescence to early adulthood in a British multiethnic cohort

Abstract: Background:Vascular and lung function develop and decline over the life course; both predict cardiovascular events and mortality but little is known of how they develop over time. We analysed their relationship in a multiethnic cohort study to test whether lung function from early adolescence to young adulthood affected vascular indices.Methods:‘DASH’ (http://dash.sphsu.mrc.ac.uk) included 6643 children aged 11–13 years in 2003; a representative 10% sample (n = 665) participated in a pilot follow-up in 2013. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…A previous cross-sectional study found a positive association of systolic BP with FEV1 in 5-year-old children [12]. Similar results were found in the Determinants of Adolescent Social Well-Being and Health (DASH) study in children aged 11-13 years [11]. Longitudinal data showed that changes in FEV1 from 11 to 23 years were associated with changes in systolic BP [11].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A previous cross-sectional study found a positive association of systolic BP with FEV1 in 5-year-old children [12]. Similar results were found in the Determinants of Adolescent Social Well-Being and Health (DASH) study in children aged 11-13 years [11]. Longitudinal data showed that changes in FEV1 from 11 to 23 years were associated with changes in systolic BP [11].…”
Section: Discussionsupporting
confidence: 75%
“…Epidemiological surveys of the past 20 years demonstrate an association between an increased prevalence of obesity and elevated blood pressure (BP) in children and adolescents [9,10]. Whether BP may be associated with lung function independent of BMI has been a matter of debate and potential physiological mechanisms remain unclear [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to the elastic properties of the vascular tree could result in a reduction in lung elastic recoil. 27,28 For example, a cross-sectional population-based study in the UK found an association between carotid augmentation index and reduced lung function (FEV 1 ) in 11-year-old children who were born preterm. 10 The authors hypothesized that alterations to elastin and collagen production during early development could explain the association between reduced lung function and stiffer blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this association is the contribution that vascular stiffness makes to the highly perfused peripheral lung. Alterations to the elastic properties of the vascular tree could result in a reduction in lung elastic recoil 27,28 . For example, a cross‐sectional population‐based study in the UK found an association between carotid augmentation index and reduced lung function (FEV 1 ) in 11‐year‐old children who were born preterm 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational studies, including 2 prospective studies, 8,9 showed inconsistent associations between pulmonary function and arterial stiffness, as measured by pulse wave velocity (PWV). 814 Longitudinal changes in PWV in relation to pulmonary function are unclear, and it remains unknown how spirometrically-defined pulmonary function and its change affect later PWV.…”
mentioning
confidence: 99%